Long‐term outcome of adjustable transobturator male system for stress urinary incontinence in the Iberian multicentre study. Issue 6 (4th June 2020) - Angulo, Javier C.; Virseda‐Chamorro, Miguel; Arance, Ignacio; Ruiz, Sonia; Ojea, Antonio; Carballo, Manuel; Rodríguez, Andrés; Pereira, Javier; Teyrouz, Antoine; Rebassa, Miguel; Escribano, Gregorio; Teba, Fernando; et al.
Abstract: Aim: The aim of this study is to evaluate long‐term durability and effectiveness of the adjustable transobturator male system (ATOMS). Materials and Methods: The retrospective multicenter Iberian ATOMS study (n = 215) was updated to evaluate long‐term continence status, complications, explants, and secondary treatments. Mean follow‐up from surgery to March 2020 was 60.6 ± 18.4 months (range, 39‐91). Eleven patients deceased of an unrelated causes. Kaplan‐Meier curves were performed to evaluate device durability and incontinence free of recurrence interval. The multivariate analysis defined the population at risk of device explant. Results: A total of 155 patients were dry at the last follow‐up visit (72.1%); 99 (46%) used no pads and 56 (26%) used a security pad/day with urine loss less than 10 mL; 96% of dry patients after adjustment remained free of incontinence 1 year later, 93.6% 2 years later, 91.1% 3 years later, 89.2% 5 years later, and 86.7% 8 years later. Complications during follow‐up occurred in 43 of 215 (20%). In total, 25 (11.6%) devices were explanted and causes were inefficacy 11 (44%), inefficacy and pain 3 (12%), port erosion 10 (40%), and wound infection 1 (4%). The secondary implant was performed in 11 (5.1%) cases, 6 artificial urinary sphincter and 5 repeated ATOMS. Time to explant was associated to complications ( P  < .0001), baseline stress urinary incontinence (SUI) severity ( P  = .01), and former irradiation ( P  = .03). Multivariate analysis revealed complications (hazard ratio [HR] = 8.71; 3.83‐19.82), baseline SUI severity (>5 compared to 1‐2 pads/day; HR = 14.9; 1.87‐125), and irradiation before ATOMS (HR = 2.26; 1.02‐5.18) predicted earlier ATOMS explant. Three cases received radiation after implant without complication. Conclusions: ATOMS device is efficacious and safe in the long term. Determinants for device explant include complications, baseline severity of incontinence, and previous irradiation. Currently, the durability of the device after 5 years is reassuring.